FACTORS RELATED TO EMPLOYEE COMPLAINTS ABOUT RESPIRATORY DISORDERS AT THE REFINERYCORN LALOLO, KARO DISTRICT YEAR 2022 - Reni Aprinawaty Sirait; Meria Turnip; Inka Ardiany Ginting (JURNAL KESMAS DAN GIZI (JKG), 2023)
Life and activities are greatly influenced by the respiratory system. Typically, mild complaints and symptoms are the first sign of respiratory tract disease. This study's objective is to identify those factors. associated with complaints of respiratory problems among workers at the Lalolo corn refinery in Karo Regency such as working hours, smoking practices, working time, and PPE use. A quantitative approach with a cross-sectional approach was used in the research. The populace and test were This study consisted of all workers at the Lalolo corn refinery in Karo Regency, namely 30 respondents. The Chi-Square test was used in data analysis. The study's findings were based on working hours exceeding eight hours, with up to 23 respondents. (76.7%), < 8 hours as many as 7 respondents (23.3%), smoking habits in the smoking category as many as 19 respondents (63.3%), the factor of working period in the category > 5 years was 22 workers and < 5 years was 8 respondents (26.7%), the fact that 17 respondents did not use personal protective equipment (43.3%) and there were 20 respondents (66.7%). The conclusion of the study was that there was a relationship between working hours, smoking habits, working period and use of PPE with complaints of respiratory problems in workers at the Lalolo corn refinery in Karo Regency.